Pengaruh Subtitusi Tepung Kacang Hijau terhadap Mutu Organoleptik dan Kadar Protein Beras Rendang - Nur Ahmad Habibi; Vara Dianti Putri; Andrafikar Andrafikar; Safyanti Safyanti; Wiwi Sartika; Kasmiyetti Kasmiyetti (Jurnal Sehat Mandiri, 2023)
Beras Rendang is one of the traditional food from West Sumatra, originating from the city of Payakumbuh. It is made with glutinous rice, which has low protein content. Substitution glutinous rice flour with mung bean flour as a protein source in Beras Rendang is expected to increase the protein content. The aim of this study is to determine the utilization of mung bean flour in the production of Beras rendang in terms of organoleptic quality and protein content. The research design used was an experimental design with a Completely Randomized Design (CRD) consisting of 4 treatments with 2 replications. The products were tested for organoleptic quality and protein content. Data analysis was performed descriptively and using a comparative test The organoleptic test data and protein content were analyzed descriptively. The results of the organoleptic test showed an overall preference of the panelists towards the color, aroma, texture, and taste, with an average score of 3.1. The best substitution of mung bean flour in terms of organoleptic quality for Beras rendang was found in treatment P1, using 100 grams of mung bean flour. The protein content in the best treatment (P1) was 8.9 grams. Substitution mung bean flour can increase the protein content, but it also affects the taste, color, texture, and aroma of the product. Therefore, other techniques are needed to improve the quality of the product.